Videogame Formalism: On Form, Aesthetic Experience and Methodology by Alex Mitchell and Jasper van Vught (Amsterdam University Press, 2023) - Hans-Joachim Backe (Eludamos)
A review of Alex Mitchell and Jasper van Vught's Videogame Formalism. On Form, Aesthetic Experience and Methodology. Published by Amsterdam University Press, 2023. ISBN: 978-9-048-55423-2, 264 pages,